Socioeconomic status as a moderator between social cognitions and physical activity: Systematic review and meta-analysis based on the Theory of Planned Behavior. - Schüz, Benjamin; Li, Arthur Sone-Wai; Hardinge, Alison; McEachan, Rosemary R.C.; Conner, Mark (Psychology of Sport & Exercise, 2017)
Background Health inequalities are to a substantial degree due to socioeconomic status (SES) related differences in health behaviors such as physical activity. However, little is known about the role SES plays in the self-regulation of physical activity. Purpose This systematic review with meta-analysis examines whether a comprehensive set of indicators of SES (income, education, occupational status) impacts on the behavioral self-regulation by moderating the relationships between social cognitions in the Theory of Planned Behavior (TPB) and physical activity. Methods A systematic literature search identified 99 studies from 88 articles that provided information on sample SES and correlations between TPB variables and physical activity. Random-effects meta-analyses were used to pool correlations corrected for sampling and measurement error. Random-effects meta-regression was used to examine moderating effects of study-level SES on these correlations. Results Education moderated the relationship between intentions and physical activity, such that studies with better educated samples reported stronger intention-physical activity relationships. Conclusions These results suggest that education might play a major role in the self-regulation of physical activity, with better educated samples more likely to translate intentions into behavior. This can both help to explain heterogeneity in the relation between intentions and physical activity as well as support the development of more effective interventions targeting intentions and physical activity.